RELIGION AS LAW: THE ISRAELI NATION- STATE LAW AND THE PALESTINIANS - Alexandria Buettner (Washington University Global Studies Law Review, 2020)
Yousef Munayyer had to travel 6,000 miles to meet his wife, who had lived 30 miles from him their entire lives.1 When the couple decides to visit their families, they cannot fly into the same airport in Tel Aviv, although it is the closest to their hometowns. Instead, she must land in a different country, while her husband is permitted to fly into Tel Aviv’s Ben-Gurion Airport.2 Should they choose to land in the closest possible airport for Munayyer’s wife, Israeli law still requires the couple take different bridges, located two hours apart, and answer a series of questions in order to be permitted to return to their childhood home together.3 Munayyer is an Arab Israeli citizen. His wife is not.4 Their realities represent the sharp divide between Israelis and Palestinians. Although Munayyer is an Arab, he was fortunate enough to obtain Israeli citizenship by virtue of his birth in the city of Lod, instead of in the occupied West Bank.5 Not all Palestinians are as lucky. Aside from the nearly 5 million Palestinian refugees eligible for aid from the United Nations, there are many more Palestinians living in the occupied territories of Israel who are subject to Israeli laws. The passage of the Israeli Nation-State Law and the actions of current United States President Donald Trump will deeply impact the Palestinians and Palestinian refugees. 6 This note will first address the background of the Palestinian Refugee crisis and the creation of the State of Israel. I will then address the impact of Israel’s Nation State law in conjunction with the growth of Israeli nationalism as well as address some, possible consequences, and steps to minimize these negative effects.
Keywords: Religion; Israeli; Palestinians